Determinants of Industry and Region Based Open Innovation in Turkey - Ümit K. Seyfettİnoğlu; Şebnem Arik; Selim Çağatay (Istanbul Business Research (IBR), 2020)
The concept of open innovation has emerged from the thought that firms and institutions do not reveal innovation solely through internal processes as in closed innovations. The process of introducing innovation is accelerated by enabling the knowledge inflow to and outflow from the company; and the competitive power is achieved not by producing the best and the greatest number of ideas/projects but by using the inner and outer ideas in the most efficient way. The literature has defined the stages of open innovation throughout the production process as idea generation, idea development, experience, engineering, manufacturing and commercialization. These stages have been labelled the depth of the firm's openness. Additionally, all possible stakeholders with whom companies can collaborate throughout the production process have been defined as the width of the firm's openness. This study econometrically identifies the factors that determine firm openness on the basis of industries and regions in Turkey. The study was conducted across 420 companies, which were among the largest 1000 companies in 2011. The theoretical basis puts forward the characteristics related to the firm's internal and external environment as well as the firm's ability to collaborate as the determinants of firm openness. In the analyses, the effects of proximity and distance-relations between regions/provinces on firm openness were determined as well, and how much and in which direction these effects deviated from the general were observed.
Keywords: 650; Inbound open innovation; Outbound open innovation; Open innovation; firm depth; firm width; Geographically weighted